Relief-oriented use of marijuana by teens - Johnson Joy L; Bottorff Joan L; Moffat Barbara M; Mulvogue Tamsin (BMC, 2009)
Abstract Background There are indications that marijuana is increasingly used to alleviate symptoms and for the treatment of a variety of medical conditions both physical and psychological. The purpose of this study was to describe the health concerns and problems that prompt some adolescents to use marijuana for therapeutic reasons, and their beliefs about the risks and benefits of the therapeutic use of marijuana. Methods As part of a larger ethnographic study of 63 adolescents who were regular marijuana users, we analyzed interviews conducted with 20 youth who self-identified as using marijuana to relieve or manage health problems. Results Thematic analysis revealed that these teens differentiated themselves from recreational users and positioned their use of marijuana for relief by emphasizing their inability to find other ways to deal with their health problems, the sophisticated ways in which they titrated their intake, and the benefits that they experienced. These teens used marijuana to gain relief from difficult feelings (including depression, anxiety and stress), sleep difficulties, problems with concentration and physical pain. Most were not overly concerned about the risks associated with using marijuana, maintaining that their use of marijuana was not 'in excess' and that their use fit into the realm of 'normal.' Conclusion Marijuana is perceived by some teens to be the only available alternative for teens experiencing difficult health problems when medical treatments have failed or when they lack access to appropriate health care.